LEGAL PROTECTION OF CUSTOMERS WHO MAKE PAYMENT THROUGH BRILINK E-BANKING (STUDY AT THE TANJUNG KARANG BRANCH OF BANK RAKYAT INDONESIA - Larakasih, Angra Adinda; B, Erlina; Hesti, Yulia (Fasanesia Library, 2019)
The development of technology is currently growing rapidly. This can be proven by advances in technology around the world. Technological progress is very important and has a very big effect on humans. Because technology is one of the supporting advances in human life. It can be proven that with the sophisticated technology, everything becomes fast and easy. The development of technological systems encourages the emergence of business opportunities in the internet field. In today's technology development it also influences the banking world. In conducting banking transactions through BRI Link agents, customers also receive protection for their rights to receive compensation for losses they have suffered. Customers as consumers of products and / or services offered by banks as producers are entitled to compensation for losses they experience when making transactions with e-banking facilities or services. Banks are required to provide compensation to customers as consumers of banking services for losses from using e-banking provided by the bank. However, it should be noted that this provision does not apply if the customer suffers a loss due to the previous customer's actions or negligence. Then the bank will solve it because the settlement of customer complaints is a form of increasing customer protection in order to guarantee customer rights in dealing with the bank.